2021
DOI: 10.3390/plants10091908
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of Cardamom (Elettaria cardamomum (L.) Maton) and Turmeric (Curcuma longa L.) Extracts for Their Applications as Natural Anti-Inflammatory Adjuvants

Abstract: The genus Zingiberaceae has been widely used for phytotherapeutic purposes in traditional medicine throughout the world for its anti-inflammatory activity. Experimental studies have established that inflammation caused by chronic infections represents a risk factor for different forms of cancer. The objective of this study was focused on determining the anti-inflammatory capacity and cytotoxic activity of aqueous extracts of Elettaria cardamomum (cardamom) and Curcuma Longa (turmeric). The extracts were obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 60 publications
0
13
0
Order By: Relevance
“…Extracts were then filtered, rotaevaporated, and stored at 4 °C in amber bottles until use. The following Formula (1) was used to calculate the extraction yield percentage [ 13 ]: …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Extracts were then filtered, rotaevaporated, and stored at 4 °C in amber bottles until use. The following Formula (1) was used to calculate the extraction yield percentage [ 13 ]: …”
Section: Methodsmentioning
confidence: 99%
“…Plants are a source of bioactive molecules with antibacterial, antiparasitic, healing, analgesic, anti-inflammatory, and tissue repairing properties, representing a potential alternative in cancer treatment [ 13 , 14 , 15 ]. Approximately 80% of developing countries’ world population adopts plants to treat various ailments [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Curcumin, demethoxycurcumin, and bisdemethoxycurcumin all suppressed NO-production as well as iNOS mRNA in activated rat primary microglial cells, showing their important role in ensuring homeostasis and cell integrity [ 27 ]. Furthermore, peritoneal macrophages were found to produce high amounts of NO after stimulation with LPS, an effect that was reversed after treatment with TE [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the detailed toxicity test, including the genetic toxicity of L. cubeba leaves, should be investigated before application in the food industry. It has been reported that α-terpinyl acetate, the major compound of MLE, reduced TNF-α and IL-6 in LPS-activated macrophages ( 42 ). In addition, 1,8-cineole, another major compound of MLE inhibited the NLRP3 inflammasome activation in macrophages ( 43 ).…”
Section: Discussionmentioning
confidence: 99%